Orbital Defect Reconstruction using Customized Implants: Current Techniques and Long-Term Outcomes in Maxillofacial Surgery. - Muñoz, Nicolay Mijail Hidrobo; Zapata, Mario Roberto Melena; Guerrero, Doménica Dayana Soto; Ortega, Erika Fernanda Miguez; Felicita, Kevin Lenin Lalangui; Jean Carlo Cedillo; Molina, Nadya Sofía Obando; Guerrero, Geovanni Xavier Guevara (International Journal of Medical Science and Dental Health, 2024)
This systematic review investigates the current methods and long-term results of maxillofacial surgery orbital defect restoration with personalized implants. PRISMA standards were followed in order to identify and analyze pertinent studies that focused on patient-specific implants (PSI) for orbital abnormalities. This was accomplished by a thorough search of multiple databases. The findings demonstrate how well PSI works to improve both functional and cosmetic outcomes, such as the correction of facial asymmetries, enophthalmos, and diplopia. Surgical navigation and 3D printing are examples of cutting-edge technology that have improved orbital defect reconstruction's precision and versatility. While some research points to a trend toward better results when using PSI as opposed to more conventional methods, additional long-term data is required to properly assess its effectiveness. The analysis highlights the role that customized implants play in attaining the best possible outcomes and urges more research to improve surgical methods and assess patient outcomes over long time frames.